Analysis of growth rate and supply response of cocoa in Tamil Nadu, India: Nerlovian adjustment model - Sundariya, M.; Banumathy, V.; Ravichandran, S. (Journal of Plantation Crops, 2022)
The present study focussed on the growth rate of area, production and productivity of cocoa in Tamil Nadu and estimated the impact of cocoa allocation decision, price variation and its supply in selected districts. The study employed the CAGR, Nerlovian model using the secondary data from 2011-12 to 2020-21. A positive significant growth in the area (40.24%) and production (34.60%) was witnessed in the Coimbatore district, while Thanjavur district showed a decline in the growth rate of cocoa. The area response concluded by lagged values of area and price significantly influenced the current year area in Coimbatore. The lagged productions were positively significant for both the districts and inferred that the increase in the price with one per cent level with the respective rise in price variability in Coimbatore district and opposite trend in Thanjavur district. The study suggested improving cocoa productivity and smoothing out variability in domestic prices can help boost farmers’ confidence in cocoa cultivation. The government provided the subsidy for transportation of the beans from one place to another, procurement centres in cocoa growing districts in Tamil Nadu and supplying the HYV to increase production, developing crop insurance schemes for cocoa during uncertain conditions and establishing facilities for the distribution of beans through Farmer Producer Companies (FPO), as well as attracting foreign consumers by improving bean quality.